Deterrence in the second nuclear age - Payne, Keith B. (University Press of Kentucky, 1996)
Keith Payne begins by asking, ""Did we really learn how to deter predictably and reliably during the Cold War?"" He answers cautiously in the negative, pointing out that we know only that our policies toward the Soviet Union did not fail. What we can be more certain of, in Payne's view, is that such policies will almost assuredly fail in the Second Nuclear Age -- a period in which direct nuclear threat between superpowers has been replaced by threats posed by regional ""rogue"" powers newly armed with chemical, biological, or nuclear weapons. The fundamental problem with deterrence theory is th